Regularization methods for accretive variational inequalities over the set of common fixed points of nonexpansive semigroups. (2nd August 2016) - Thuy, Nguyen Thi Thu; Hieu, Pham Thanh; Strodiot, Jean Jacques
Abstract : In this paper, we introduce a regularization method based on the Browder–Tikhonov regularization method for solving a class of accretive variational inequalities over the set of common fixed points of a nonexpansive semigroup on a uniformly smooth Banach space. Three algorithms based on this regularization method are given and their strong convergence is studied. Finally, a finite-dimensional example is developed to illustrate the numerical behaviour of the algorithms.